Nanofiber membrane as well as preparation method and application thereof
By using nanofiber membranes composed of nanofibers such as polyamide, polyethylene oxide and cellulose acetate, the problem of poor filtration of nano-scale particles by traditional fiber membranes is solved, and efficient nano/microparticle filtration and long-lasting Filtration performance.
Patent Information
- Application Number
- CN202411197362.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional fiber membranes have poor filtration effects on nano-scale particles, and the filtration efficiency of charged fiber membranes decreases over time, making it difficult to maintain long-lasting filtration performance.
Nanofibers composed of nanofiber films such as polyamide, polyethylene oxide and cellulose acetate were prepared by electrospinning method, and nanofibers with diameters of ≤100nm accounted for 30% to 75% of the total fiber count, forming a high proportion. Membrane structure with surface area and small pore size.
It significantly improves the filtration effect of nano/micron particles, the filtration efficiency can reach more than 95%, maintains a high quality factor, and is suitable for the field of air filtration.
Smart Images

Figure CN119121510A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber membranes, and in particular to a nano fiber membrane and a preparation method and application thereof. Background Art
[0002] In recent years, although the industrialization and urbanization process in various countries has promoted the rapid development of the global economy, it has also brought air pollution that is harmful to human health. Air pollutants are mainly particles with a size of less than 2.5μm (commonly known as PM2.5), which are suspended in the air in the form of aerosols. These particles have a high specific surface area, stay in the atmosphere for a long time, easily absorb harmful substances, and enter the blood or deposit in the lungs through the cilia in the nostrils as people breathe. People who are exposed to air pollution for a long time are prone to various respiratory and cardiovascular diseases, and even cause lung cancer and premature death, which brings great harm to human health. Traditional air filter materials can have a certain filtering effect on micron-sized particles, but have a poor filtering effect on nano-sized particles. Electrospinning is a simple and inexpensive technology that can develop nanofiber membranes with much smaller diameters than traditional fibers. These nanofiber membranes have the advantages of small pore size and high porosity, can effectively capture and intercept nano / micron particles at a small thickness, and have broad application prospects in the field of air filtration. At present, the use of electrospinning technology to prepare nanofiber membranes for high-efficiency air filtration is the focus of development in this technology field.
[0003] In order to improve the filtration performance of fiber membranes, many research reports have reported that the filtration efficiency of nanofiber membranes can be improved by adjusting their structure and performance. Adding electret particles to the spinning solution allows the fibers to carry charges, and the ability of the fibers to capture particles is improved through electrostatic adsorption, so that the fiber membranes can obtain higher filtration efficiency at lower pressure drops, increase the quality factor, and improve the filtration performance. However, the charges carried by the fiber membranes prepared by these methods are not persistent. As time goes by, the fiber's ability to capture particles rapidly weakens, the filtration efficiency decreases, resulting in a decrease in the quality factor, and it is difficult to maintain lasting filtration performance.
[0004] Therefore, it is necessary to develop nanofiber membranes for high-efficiency air filtration. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a nanofiber membrane having excellent filtration performance and quality factor.
[0006] A second aspect of the present invention provides a method for preparing a nanofiber membrane.
[0007] A third aspect of the present invention provides an application of a nanofiber membrane.
[0008] According to a first aspect of the present invention, an embodiment provides a nanofiber membrane, which includes polyamide nanofibers, polyethylene oxide nanofibers and cellulose acetate nanofibers; wherein nanofibers with a diameter of ≤100 nm account for 30% to 75% of the total fiber number of the nanofiber membrane.
[0009] The nanofiber membrane according to the embodiment of the present invention has at least the following beneficial effects:
[0010] The nanofiber membrane of the present invention is composed of three types of nanofibers, namely polyamide nanofibers, polyethylene oxide nanofibers and cellulose acetate nanofibers. It is limited that the nanofibers with a diameter of ≤100nm account for 30% to 75% of the total number of fibers in the nanofiber membrane. Therefore, the nanofiber membrane of the present invention has a high specific surface area, a small pore size and an interconnected pore structure, which greatly improves the filtering effect of nano / micron particles while maintaining the mechanical properties of the membrane, and the filtering efficiency of particulate matter can reach more than 95%; it has broad application prospects in the field of air filtration.
[0011] According to some embodiments of the present invention, the average diameter of the polyamide nanofibers is 5 to 50 nm.
[0012] According to some embodiments of the present invention, the average diameter of the polyethylene oxide nanofibers is 80-200 nm.
[0013] According to some embodiments of the present invention, the average diameter of the cellulose acetate nanofibers is 400-800 nm.
[0014] According to some embodiments of the present invention, the average diameter and the percentage of nanofibers with a diameter of ≤100 nm in the present invention to the total number of fibers in the nanofiber membrane are calculated by the following method:
[0015] Fiber membranes from five different regions were randomly selected for electron microscopy. The diameter of each fiber was measured on the electron microscopy image using Image-pro Plus 6.0 software, and the average fiber value and the proportion C of nanofibers with a diameter below 100 nm were calculated.
[0016]
[0017] Where A is the number of nanofibers with a diameter less than 100 nm in the membrane; B is the total number of fibers in the membrane.
[0018] According to some embodiments of the present invention, at an air flow rate of 85 L / min, the filtration efficiency of the nanofiber membrane is ≥ 95%; the quality factor is 0.0165-0.0500 Pa -1 .
[0019] According to some embodiments of the present invention, the filtration efficiency and quality factor are tested and calculated by the following method:
[0020] The nanofiber membrane was inserted into two layers of non-woven fabric with negligible filtration efficiency (filtration efficiency was 2.62% at an airflow of 85 L / min) to construct a sandwich-structured nanofiber membrane / non-woven fabric composite material for measuring air filtration performance. According to the national standard "GB 19083-2010 Technical Requirements for Medical Protective Masks", the airflow rate was selected to be 85 L / min when testing the filtration performance of the fiber membrane / non-woven fabric composite material. A NaCl solution with a concentration of 0.02 g / mL was loaded into the aerosol generator of the TSI8130 filter instrument, which generated NaCl aerosols with a mass median particle size of 260 nm and a number median particle size of 75 nm. The airflow passed from the upstream through an effective area of 100 cm 2 The fiber membrane / nonwoven fabric composite material enters the downstream, and after the filtration test is completed, the filtration efficiency η and pressure drop ΔP of the nanofiber membrane can be obtained. Repeat the test of 5 samples under the same preparation conditions, take the average value as the final test result, and then calculate the quality factor QF of the nanofiber membrane using the following formula.
[0021]
[0022] According to some embodiments of the present invention, a method for preparing a nanofiber membrane is provided, comprising the following steps:
[0023] S1. Mixing cellulose acetate, polyethylene oxide, polyamide and a mixed solvent to obtain a spinning solution:
[0024] S2, spinning the spinning solution by electrospinning to obtain a nanofiber membrane;
[0025] Wherein, the mixed solvent includes formic acid and acetic acid.
[0026] The method for preparing the nanofiber membrane according to the embodiment of the present invention has at least the following beneficial effects:
[0027] The present invention uses formic acid and acetic acid as a mixed solvent. Cellulose acetate, polyethylene oxide and polyamide are separated into three phases in the mixed solvent due to the differences in molecular structures and properties of the three polymers and the two-component solvent. The nanofiber membrane prepared by the electrospinning method has excellent filtration efficiency.
[0028] According to some embodiments of the present invention, the mass ratio of formic acid to acetic acid is (1-4): 1. Thus, the content of nanofibers with a diameter less than 100 nm can be increased by adjusting the content of acetic acid.
[0029] According to some embodiments of the present invention, the mass ratio of polyethylene oxide, cellulose acetate and polyamide is 1:5:(2-5). Thus, the content of nanofibers with a diameter less than 100 nm can be increased by adjusting the content of polyamide.
[0030] According to some embodiments of the present invention, the process conditions of the electrospinning include:
[0031] The spinning liquid flow rate is 0.2-2 mL / h, the spinning voltage is 15-30 kV, the spinning receiving distance is 10-20 cm, the spinning time is 24 min-60 min, the temperature is 20-40° C., and the relative humidity is 30-80%.
[0032] According to some embodiments of the present invention, the weight average molecular weight of the cellulose acetate is 30,000 to 80,000.
[0033] According to some embodiments of the present invention, the weight average molecular weight of the polyethylene oxide is 100,000 to 1,000,000.
[0034] According to some embodiments of the present invention, the polyamide is selected from polyamide 6 and / or polyamide 66.
[0035] The third aspect of the present invention provides an application of the nanofiber membrane described in the first aspect of the present invention in air filtration.
[0036] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0038] Figure 1 This is an electron microscope image of the nanofiber membrane prepared in Example 1.
[0039] Figure 2 This is an electron microscope image of the nanofiber membrane prepared in Example 1 after filtration. DETAILED DESCRIPTION
[0040] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0041] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0042] Some of the raw materials in the embodiments of the present invention are as follows:
[0043] Polyamide: Polyamide-6; the molecular structure is -[NH-(CH2)-CO]- n , purchased from Suzhou Yaco Chemical Reagent Co., Ltd.;
[0044] Polyethylene oxide: weight average molecular weight Mw = 300000, purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0045] Cellulose acetate: cellulose diacetate; weight average molecular weight Mw = 40000, purchased from Shanghai Ole Chemical Co., Ltd.;
[0046] The specific test methods for the average fiber diameter and the proportion of nanofibers with a diameter less than 100 nm in the following examples and the particle filtration efficiency of the nanofiber membrane are as follows:
[0047] (1) Test method for average fiber diameter and percentage of nanofibers with diameters below 100 nm: Fiber membranes from five different regions were randomly selected for electron microscopy. The diameter of each fiber was measured on the electron microscopy image using Image-pro Plus 6.0 software. The average fiber value and percentage C of nanofibers with diameters below 100 nm were calculated.
[0048]
[0049] Where A is the number of nanofibers with a diameter less than 100 nm in the membrane; B is the total number of fibers in the membrane.
[0050] (2) Determination of particle filtration efficiency and quality factor of nanofiber membrane: A multi-level structure of diacetyl cellulose / polyethylene oxide / polyamide-6 nanofiber membrane was inserted into two layers of non-woven fabric with negligible filtration efficiency (filtration efficiency was 2.62% at an airflow of 85 L / min) to construct a sandwich structure of nanofiber membrane / non-woven fabric composite material for measuring air filtration performance. According to the national standard "GB 19083-2010 Technical Requirements for Medical Protective Masks", the airflow rate was selected to be 85 L / min when testing the filtration performance of the fiber membrane / non-woven fabric composite material. A NaCl solution with a concentration of 0.02 g / mL was loaded into the aerosol generator of the TSI8130 filter material instrument, which generated NaCl aerosol with a mass median particle size of 260 nm and a number median particle size of 75 nm. The airflow passed from the upstream through an effective area of 100 cm 2 The fiber membrane / nonwoven fabric composite material enters the downstream, and after the filtration test is completed, the filtration efficiency η and pressure drop ΔP of the composite material can be obtained. Repeat the test of 5 samples under the same preparation conditions, take the average value as the final test result, and then use the following formula to calculate the quality factor QF of the composite material. The test data results are shown in Table 1.
[0051]
[0052] Example 1
[0053] This example provides a nanofiber membrane, and the preparation method thereof is as follows:
[0054] S1. At room temperature, cellulose diacetate powder, polyethylene oxide powder and polyamide-6 particles are respectively placed in a formic acid / acetic acid two-component solvent with a mass ratio of 1:1 at a mass ratio of 5:1:5, and stirred at room temperature for 3 hours until the solution is clear to obtain a spinning solution with a concentration of 9 wt.%;
[0055] S2. In an atmospheric environment with a temperature of 25°C and a humidity of 60%, the spinning solution newly prepared in the above step S1 is loaded into a syringe and fixed on a flow pump. The spinning time is set to 36 min. The spinning solution is squeezed out from the 10mL syringe needle at a speed of 0.5mL / h, and is accelerated forward by the electrostatic field force of 21kV, and finally falls on a metal receiving roller 15cm away from the syringe needle, thereby obtaining a nanofiber membrane.
[0056] The nanofiber membrane obtained in Example 1 was tested by scanning electron microscopy, and the results are as follows: Figure 1 As shown, from Figure 1 It can be seen that there are three types of nanofibers in the fiber membrane: polyamide-6 nanofibers with an average diameter of about 39 nm, polyethylene oxide nanofibers with an average diameter of about 133 nm, and cellulose diacetate nanofibers with an average diameter of about 546 nm, of which nanofibers with a diameter less than 100 nm account for 74.4%.
[0057] Example 2
[0058] This example provides a nanofiber membrane, and the preparation method thereof is as follows:
[0059] S1. At room temperature, cellulose diacetate powder, polyethylene oxide powder and polyamide-6 particles are respectively placed in a formic acid / acetic acid two-component solvent with a mass ratio of 1:1 at a mass ratio of 5:1:4, and stirred at room temperature for 3 hours until the solution is clear to obtain a cellulose diacetate / polyethylene oxide / polyamide-6 spinning solution with a concentration of 9wt%.
[0060] S2. In an atmospheric environment with a temperature of 25°C and a humidity of 60%, the newly prepared solution in the above step S1 is loaded into a syringe and fixed on a flow pump. The spinning time is set to 60 min. The spinning solution is extruded from a 10mL syringe needle at a speed of 0.5mL / h, and is accelerated forward by the electrostatic field force of 21kV, and finally falls on a metal receiving roller 15cm away from the syringe needle, thereby obtaining a nanofiber membrane.
[0061] There are three types of nanofibers in the fiber membrane prepared in this embodiment: polyamide-6 nanofibers with an average diameter of about 41nm, polyethylene oxide nanofibers with an average diameter of about 121nm, and cellulose diacetate nanofibers with an average diameter of about 462nm, among which nanofibers with a diameter less than 100nm account for 61.2%.
[0062] Example 3
[0063] This example provides a nanofiber membrane, and the preparation method thereof is as follows:
[0064] S1. At room temperature, cellulose diacetate powder, polyethylene oxide powder and polyamide-6 particles are respectively placed in a formic acid / acetic acid two-component solvent with a mass ratio of 1:1 at a mass ratio of 5:1:3, and stirred at room temperature for 3 hours until the solution is clear to obtain a cellulose diacetate / polyethylene oxide / polyamide-6 spinning solution with a concentration of 9wt%.
[0065] S2. Step S2 is the same as step S2 in Example 1.
[0066] The nanofiber membrane prepared in this embodiment includes polyamide-6 nanofibers with an average diameter of about 46 nm, polyethylene oxide nanofibers with an average diameter of about 111 nm, and cellulose diacetate nanofibers with an average diameter of about 497 nm, of which nanofibers with a diameter less than 100 nm account for 43.5%.
[0067] Example 4
[0068] This example provides a nanofiber membrane, and the preparation method thereof is as follows:
[0069] S1. At room temperature, cellulose diacetate powder, polyethylene oxide powder and polyamide-6 particles are respectively placed in a formic acid / acetic acid two-component solvent with a mass ratio of 1.5:1 at a mass ratio of 5:1:5, and stirred at room temperature for 3 hours until the solution is clear to obtain a spinning solution with a concentration of 9wt%.
[0070] S2. Step S2 is the same as step S2 in Example 2.
[0071] In this case, there are three types of nanofibers in the fiber membrane: polyamide-6 nanofibers with an average diameter of about 52 nm, polyethylene oxide nanofibers with an average diameter of about 107 nm, and cellulose diacetate nanofibers with an average diameter of about 507 nm. Nanofibers with a diameter less than 100 nm account for 54.5%.
[0072] Example 5
[0073] This example provides a nanofiber membrane, and the preparation method thereof is as follows:
[0074] S1. At room temperature, cellulose diacetate powder, polyethylene oxide powder and polyamide-6 particles are respectively placed in a formic acid / acetic acid two-component solvent with a mass ratio of 1:1 at a mass ratio of 5:1:5, and stirred at room temperature for 3 hours until the solution is clear to obtain a spinning solution with a concentration of 9wt%.
[0075] S2. Step S2 is the same as step S2 in Example 2.
[0076] There are three types of nanofibers in the fiber membrane prepared in this embodiment: polyamide-6 nanofibers with an average diameter of about 39 nm, polyethylene oxide nanofibers with an average diameter of about 133 nm, and cellulose diacetate nanofibers with an average diameter of about 546 nm. Nanofibers with a diameter less than 100 nm account for 74.4%.
[0077] Comparative Example 1
[0078] This example provides a nanofiber membrane, and the preparation method thereof is as follows:
[0079] S1. At room temperature, cellulose diacetate powder and polyethylene oxide powder are respectively placed in a formic acid / acetic acid two-component solvent with a mass ratio of 1:1 in a mass ratio, and stirred at room temperature for 3 hours until the solution becomes clear, to obtain a spinning solution with a concentration of 9 wt%;
[0080] S2. Step S2 is the same as step S2 in Example 2.
[0081] There are two types of nanofibers in the fiber membrane prepared in this embodiment: the average diameter of polyethylene oxide nanofibers is 86nm, and the average diameter of cellulose diacetate nanofibers is about 546nm, of which nanofibers with a diameter less than 100nm account for 15.7%.
[0082] Performance Testing
[0083] The filtration efficiency and quality factor of the nanofiber membranes prepared in the examples and comparative examples of the present invention were tested, and the results are shown in Table 1.
[0084] Table 1 Examples 1 to 5 and Comparative Example 1
[0085] Filtration efficiency / % <![CDATA[Quality factor Pa -1 > Example 1 96.13 0.02422 Example 2 98.06 0.01965 Example 3 95.43 0.01653 Example 4 97.54 0.01683 Example 5 99.59 0.02189 Comparative Example 1 88.07 0.01594
[0086] From the data in Table 1, in implementation cases 2, 3 and 5, the mass ratios of cellulose diacetate, polyethylene oxide and polyamide-6 are 5:1:4, 5:1:3 and 5:1:5 respectively, the mass ratio of formic acid / acetic acid is 1:1, the spinning time is 60 min, and the corresponding filtration efficiencies of the prepared multi-level structure fiber membranes are 98.06%, 95.43% and 99.59%, and the corresponding quality factors are 0.01965Pa -1 、0.01653Pa -1and 0.02189Pa -1 In Example 4, the mass ratios of cellulose diacetate, polyethylene oxide and polyamide-6 were 5:1:5, the mass ratio of formic acid / acetic acid was 1.5:1, the spinning time was 60 min, and the filtration efficiency of the prepared multi-level structure fiber membrane was 95.43%, and the corresponding quality factor was 0.01653 Pa. -1 In comparative example 1, the mass ratio of formic acid / acetic acid and the spinning time are the same as those in examples 2, 3 and 5, but the polymer lacks the polyamide-6 component, and the filtration efficiency of the prepared fiber membrane is only 88.07%, and the quality factor is 0.01594Pa -1 . By comparison, it was found that under the same spinning time, the filtration efficiency and quality factor of the multi-level structure cellulose diacetate / polyethylene oxide / polyamide-6 nanofiber membrane prepared with different mass ratios of formic acid / acetic acid as solvent were higher than those of the cellulose diacetate / polyethylene oxide nanofiber membrane without polyamide-6. The increase in the filtration efficiency of the multi-level structure nanofiber membrane is because the addition of polyamide-6 introduces nanofibers with a diameter of 5 to 50 nm into the membrane, so that the proportion of fine nanofibers with a diameter of less than 100 nm in the membrane reaches 43.5%, or even as high as 74.4%, while the proportion of 100 nm fine nanofibers in the nanofiber membrane without polyamide-6 is only 15.7%. These fine fibers with a diameter of less than 100 nm have a higher specific surface area, which increases the fiber membrane's ability to capture particles, and also increases the probability of particles colliding and depositing on the fiber surface through the Brownian effect and interception effect, and the filtration efficiency of the multi-level structure fiber membrane is increased.
[0087] In terms of quality factor, the quality factors of these fiber membranes with multi-level structures are higher than those of cellulose diacetate / polyethylene oxide fiber membranes, indicating that the growth rate of the filtration efficiency of the multi-level structure nanofiber membrane is higher than the pressure drop, which increases the quality factor and improves the filtration performance.
[0088] In order to further verify the effect of the thickness of the multi-level structure fiber membrane on the membrane filtration performance, the spinning time was reduced from 60 min to 36 min. It was found that the filtration efficiency of the multi-level structure nanofiber membrane with a small thickness was as high as 96.13%, and the quality factor was as high as 0.02422Pa. -1 The filtration performance is significantly better than that of the thicker cellulose diacetate / polyethylene oxide nanofiber membrane, which shows that the multi-level structure fiber membrane of the present invention exhibits high efficiency at a smaller thickness and is suitable for air filtration.
[0089] Furthermore, the nanofiber membrane of Example 1 of the present invention was filtered and then subjected to a scanning electron microscope test, and the results are as follows: Figure 2 As shown, from Figure 2It can be seen that a large amount of nanoparticles are adsorbed on the surface of fine fibers in the multi-level structure fiber membrane prepared in this example, indicating that the fiber membrane can effectively capture nano-micron particles.
[0090] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A nanofiber membrane, It is characterized in that The nanofiber membrane comprises polyamide nanofibers, polyethylene oxide nanofibers and cellulose acetate nanofibers; wherein the nanofibers with a diameter of ≤100nm account for 30% to 75% of the total fiber quantity of the nanofiber membrane.
2. The nanofiber membrane according to claim 1, It is characterized in that The average diameter of the polyamide nanofibers is 5 to 50 nm.
3. The nanofiber membrane according to claim 1 or 2, It is characterized in that The average diameter of the polyethylene oxide nanofibers is 80-200 nm.
4. The nanofiber membrane according to any one of claims 1 to 3, It is characterized in that The average diameter of the cellulose acetate nanofibers is 400-800 nm.
5. The nanofiber membrane according to claim 4, It is characterized in that At an air flow rate of 85 L / min, the filtration efficiency of the nanofiber membrane is ≥95%; the quality factor is 0.0165-0.0500 Pa -1 .
6. The method for preparing a nanofiber membrane according to any one of claims 1 to 5, It is characterized in that The steps include: S1. Mixing cellulose acetate, polyethylene oxide, polyamide and a mixed solvent to obtain a spinning solution: S2, spinning the spinning solution by electrospinning to obtain a nanofiber membrane; Wherein, the mixed solvent includes formic acid and acetic acid.
7. The method for preparing the nanofiber membrane according to claim 6, It is characterized in that The mass ratio of formic acid to acetic acid is (1-4):
1.
8. The method for preparing the nanofiber membrane according to claim 6, It is characterized in that The mass ratio of the polyethylene oxide, cellulose acetate and polyamide is 1:5:(2-5).
9. The method for preparing the nanofiber membrane according to claim 6, It is characterized in that The process conditions of the electrospinning include: The spinning liquid flow rate is 0.2-2 mL / h, the spinning voltage is 15-30 kV, the spinning receiving distance is 10-20 cm, the spinning time is 24 min-60 min, the temperature is 20-40° C., and the relative humidity is 30-80%.
10. Use of the nanofiber membrane according to any one of claims 1 to 5 in air filtration.
Citation Information
Patent Citations
Four-layer composite micro-nano fibrous air filtration membrane and application thereof
CN109012218A
Polyamide / cellulose acetate multistage fiber composite cigarette film and preparation method and application thereof
CN116328560A
Hollow fibre filter nano membrane and its preparing process
CN1372999A
Filter medium for filter and method for producing the same
JP2014200701A
Filter materials and filters made therefrom
WO2015150718A1
